PENGARUH BRAND LOVE TERHADAP BRAND LOYALTYDAN WILLINGNESS TO PAY PREMIUM PRICE(Studi Pada Konsumen Starbucks di Kota Surabaya) - M. Ivan Efendi; Siti Ning Farida (Jurnal Ekonomi dan Bisnis (EK dan BI), 2021)
Brands have an important role for the continuity of a business, because current and future marketing is a competition between brands to seize consumers through brands. Brand love is a market phenomenon that refers to the deep or intense emotions a customer experiences in relation to a particular brand. This emotional attachment can later make consumers loyal to a brand. This study aims to determine the effect of brand love on brand loyalty and willingness to pay premium price of Starbucks consumers in Surabaya. The research method used is quantitative methods. The population in this study were Starbucks consumers in Surabaya. The number of samples used was 100 respondents using purposive sampling method. The data testing method used are validity and reliability test. The data analysis technique used is the structural equation model partial least square (SEM PLS). Calculation of data using Smart PLS ver. 3. Based on the research results, it can be seen that brand love has a positive effect on brand loyalty, brand loyalty has a positive effect on willingness to pay premium price, and brand love has a positive effect on willingness to pay premium price for Starbucks consumers in Surabaya.